Trastuzumab-based regimens beyond progression: A crucial treatment option for HER2+ advanced/metastatic breast cancer - Thibaut Sanglier; Ryan Ross; Tianlai Shi; João Mouta; Sandra Swain; Fatima Cardoso (Breast, 2022)
Upon its establishment for the treatment of metastatic breast cancer (mBC), continuing trastuzumab beyond disease progression was an important paradigm shift that became the recommendation by major guidelines. However, data supporting continuation of human epidermal growth factor receptor 2 (HER2) blockade with trastuzumab beyond the second-line setting are limited, resulting in a lack of approval of, or access to, this therapeutic strategy in many countries. This study aimed to provide additional data on the continued use of trastuzumab and trastuzumab-based therapies in combination with chemotherapy (CT) as third-line treatment for patients with mBC. This open-cohort, retrospective, observational study used deidentified patient-level data from an electronic health record–derived database that included patients with mBC who initiated third-line treatment with trastuzumab-based therapy combined with CT (Tras + CT; n = 288) or CT alone (CT; n = 49). Patients who received Tras + CT had a longer weighted median overall survival vs those who received CT only: 20.6 months (95% CI, 18.3–26.4 months) vs 10.1 months (95% CI, 7.8–12.3 months), respectively (hazard ratio [HR], 0.29; 95% CI, 0.16–0.53). This study provides additional support for maintaining trastuzumab-based therapies for patients with HER2+ mBC beyond second-line treatment. This treatment option should be available for all patients with mBC worldwide.